Fast physical progress periods in youth women`s tennis - Skorodumova, A. P.; Semenova, S. D.; Dolgikh, N. S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to find the sensitive physical progress periods in the 6-14-year-old women players trained in the beginner and basic training groups. Methods and structure of the study. The physical fitness test set we used in the present study was developed based on the prior research findings implemented in practice as a basis for the age-, gender- and skills-specific training systems, with a high priority to the competitive progress securing physical fitness tests. We sampled for the study the 6-14 year-old girls (n=228) from seven tennis schools, academies and clubs in Moscow, Moscow Oblast and Tatarstan and split them up into nine age groups of 20-plus people each. Results and conclusion. The tests showed the physical fitness growth with age with the only exclusion for the shoulder girdle flexibility rating stick twist test. It should be emphasized, however, that the 14-year-olds were not the best in every test. The test data are indicative of the 6-14-year-old girls reaching the physical fitness peak points in the tests at different times and in different physical fitness qualities. Moreover, the peak reaching inconsistency was found in every test rating the same physical quality.